2005
DOI: 10.1093/jxb/eri228
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the glutathione redox state improve apical meristem structure and somatic embryo quality in white spruce (Picea glauca)

Abstract: In white spruce, an improvement of somatic embryo number and quality can be achieved through experimental manipulations of the endogenous levels of reduced (GSH) and oxidized (GSSG) glutathione. An optimal protocol for embryo production included an initial application of GSH in the maturation medium, followed by replacement with GSSG during the remaining maturation period. Under these conditions, the overall embryo population more than doubled, and the percentage of fully developed embryos increased from 22% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 29 publications
1
52
1
2
Order By: Relevance
“…5B), which implies that AtGSTU17 can contribute to the regulation of the GSH/GSSG ratio; a high GSH/GSSG ratio is essential for cell division (Belmonte et al, 2005). However, AtGSTU17 in the dark may have a redundant effect with other GST members on GSH/GSSG ratio for hypocotyl elongation, which led to atgstu17 having a GSH/GSSG ratio similar to that of Col (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…5B), which implies that AtGSTU17 can contribute to the regulation of the GSH/GSSG ratio; a high GSH/GSSG ratio is essential for cell division (Belmonte et al, 2005). However, AtGSTU17 in the dark may have a redundant effect with other GST members on GSH/GSSG ratio for hypocotyl elongation, which led to atgstu17 having a GSH/GSSG ratio similar to that of Col (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Bashandy et al (2010) reported that mutations of two key thiol reduction pathways, thioredoxin and GSH (the ntra ntrb cad2 mutant), resulted in a loss of auxin-regulated phenotypes such as apical dominance, vasculature, and secondary root production, and auxin transport and auxin levels, which implies that the GSH pool within cells is linked to auxin homeostasis. Moreover, alterations of the GSH redox state can improve apical meristem structure and somatic embryo quality in white spruce (Picea glauca; Belmonte et al, 2005). AtGSTU17, encoding a U class member of GST, has GST activity (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of hydrogen peroxide and its regulation by the activation of antioxidant enzymes have been recorded at the beginning of SE formation (Lilik et al 2005;Ma et al 2012a, b). It was also shown that the redox state of the culture medium had an important effect on Norway spruce embryo yield and quality (Belmonte et al 2005). Based in these observations we can discuss that the presence of OsmC protein in somatic embryos initiated at high temperature could be helpful for cell development of a redox homeostasis system and maintenance of cell differentiation.…”
Section: Discussionmentioning
confidence: 78%
“…The GSH/GSSG ratio clearly influences the cell-cycle progression. A high GSH/GSSG ratio is essential for cell division and proliferation during the initial stages of embryo development, but later in development the redox status of the glutathione pool decreases (Belmonte et al 2005). Studies using a GSH-deficient mutant or L-butathione-[S,R]-sulfoximine (BSO; an inhibitor of GSH biosynthesis) treatments suggest that GSH plays a key role in promoting signals which permit cell-cycle progression in roots and hence root growth (Vernoux et al 2000, Maughan andFoyer 2006).…”
Section: Introductionmentioning
confidence: 99%